Success conditional features: an analysis of the wind power projects of reserve energy of ANEEL - Caldas, Antonio Vinicius Silva; Silva Junior, Antônio Francisco de Almeida da (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
This study estimated the characteristic features of successful wind power projects, considering only the final data of the reserve energy auctions. Thus, we analyzed the results of 150 projects that won the competition between 2011 and 2015. We used PCA to identify the features that differentiated the projects that became plants from those that failed in this regard. We calculated scores for each project analyzed, with a cut-off date of August 2019. Among the projects that had the largest investments and proposed to generate more electricity, 90.91% were successful. We found out that the percentage of negative goodwill did not have a significant relationship with the success or failure of turning projects into plants.